2017
DOI: 10.1063/1.4973520
|View full text |Cite
|
Sign up to set email alerts
|

Dual phase grating interferometer for tunable dark-field sensitivity

Abstract: Hard X-ray dark-field and phase contrast imaging using grating interferometry have shown great potential for medical and industrial applications. However, the wide spread applicability of the method is challenged by a number of technical related issues such as relatively low dose and flux efficiency due to the absorption grating, fabrication of high quality absorption gratings, slow data acquisition protocol and high mechanical stability requirements. In this paper, the authors propose an interferometric metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 26 publications
0
65
0
Order By: Relevance
“…[32][33][34][35] Darkfield imaging can also provide 3D microstructural information in tomographic mode. [36][37][38] Colloidal systems [39][40][41][42][43][44] and powders 45 were investigated with this imaging method to demonstrate its capability to provide quantitative results for example on the radius size of the colloid particles. Yang et al 46 showed that X-ray dark-field imaging is able to visualize the transport of water in thin samples (2 mm) of porous mortar.…”
mentioning
confidence: 99%
“…[32][33][34][35] Darkfield imaging can also provide 3D microstructural information in tomographic mode. [36][37][38] Colloidal systems [39][40][41][42][43][44] and powders 45 were investigated with this imaging method to demonstrate its capability to provide quantitative results for example on the radius size of the colloid particles. Yang et al 46 showed that X-ray dark-field imaging is able to visualize the transport of water in thin samples (2 mm) of porous mortar.…”
mentioning
confidence: 99%
“…The combination of unconventional processing and the freedom from microelectronics constrains enrich the spectrum of capabilities and give a new life to the "old silicon material", with revolutionizing advancements in nanotechnology [37]. We recently reported about micro-and nano-fabrication processing for X-ray gratings, including lithography [89], dry [37,90,91] and wet etching methods [39], Au electroplating [22], Ir atomic layer deposition [92] and metal casting [19,20]. The use of MacEtch as a microfabrication process for X-ray optical devices was first reported in 2014 for Fresnel zone plate structures [17,18].…”
Section: Silicon Based Microfabrication Of X-ray Opticsmentioning
confidence: 99%
“…The fabricated gratings have been successfully applied in a recently developed x-ray interferometer based on two phase shifting gratings that can be used for differential phase contrast as well as dark-field X-ray imaging. A thorough description of the interferometer can be found here [3]. The experimental setup is presented in Figure 5.…”
Section: X-ray Imaging Experimentsmentioning
confidence: 99%